Association between arterial stiffness and obstructive sleep apnea in patients with arterial hypertension and continuous positive airway pressure therapy. Issue 5 (8th December 2020) - Sirenko, Yu; Krushynska, N; Rekovets, O; Torbas, O; Kushnir, S
No abstract available